1999
DOI: 10.1007/s004260050040
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence on the effects of symbolic distance on Stroop-like interference

Abstract: Pavese and UmiltaÁ found that, in an enumeration task, Stroop-like interference is larger when the digit identity is symbolically close to the enumeration response than when it is symbolically far. In two experiments testing 49 undergraduates, we further explored this phenomenon using Francolini and Egeth's paradigm. We found that symbolic distance aected interference even when the stimulus was brie¯y presented and masked. In Exp. 2, which tested numerosities outside the subitizing range, individuals used a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 35 publications
2
34
1
Order By: Relevance
“…Moreover, we found that the observed effect was not modulated by the symbolic distance effect, as in the classical numerical Stroop effect (Pavese & Umiltà, 1998, 1999), and it could not reduce to the computation of number from the singular or plural noun forms (Berent et al, 2005). …”
Section: Resultsmentioning
confidence: 72%
“…Moreover, we found that the observed effect was not modulated by the symbolic distance effect, as in the classical numerical Stroop effect (Pavese & Umiltà, 1998, 1999), and it could not reduce to the computation of number from the singular or plural noun forms (Berent et al, 2005). …”
Section: Resultsmentioning
confidence: 72%
“…The Number-Stroop Counting Task. The number-Stroop counting task was adapted from the task administrated in Pavese and Umilta's (1999) study. Stimuli were patterns of one-, two-, three-, four-, five-, or sixnumeral 1s, 2s, 3s, 4s, 5s, and 6s.…”
Section: Methodsmentioning
confidence: 99%
“…Pavese and Umiltà [50,51] investigated the effect of symbolic distance between the two dimensions of a stimulus (i.e., relevant and irrelevant) in an enumeration Stroop resembling the one used in the current study (the task is presented in the section below). They found that the greater the numerical distance between the two numbers in the stimulus, the shorter the RT.…”
Section: Introductionmentioning
confidence: 99%